Inequities in child protective services contact between black and white children - Thomas, Margaret M. C. (Child maltreatment, 2023)
Child protective services (CPS) contact occurs at substantially higher rates among Black than White families. The present study considers systemic racism as a central driver of this disparity and emphasizes racialized poverty as a possible mechanism. We used data from the Fragile Families and Child Wellbeing Study and logistic regression analyses to assess the associations between income poverty, a racialized experience, and CPS contact, separately among Black and White families. Results indicated that income poverty was a significant predictor of CPS contact among White families, who were protected by higher income. In contrast, income per se was not a significant predictor of CPS contact among Black families, who were instead impacted by racialized family regulation and consequences of poverty, such as poor health and depression. Refundable state Earned Income Tax Credit (EITC) policies were protective for Black families, and more expansive Temporary Assistance for Needy Families (TANF) programs decreased CPS contact for Black and White families. Implications include centering systemic racism and specifically racialized poverty as causes of racial inequities in CPS contact and rethinking the role of CPS in protecting children.